MENYIKAPI KRITIK EPISTEMOLOGI STUDI HADIS - Idri Idri (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2013)
The epistemology of Hadith studies that has been built in the history of Muslim civilization since the beginning of Islam until now with the structure of riwayah and dirayah Hadith study as well as its various branches, has provided a significant contribution to the critique and research of the Prophet Hadith authenticity. Through variety of concepts and theories in ulum al-Hadfts, Muslims can distinguish between authentic Hadiths, which are coming from the Prophet and those are not, in terms of sanad, matan, or both, so it can also be determined whether the Hadiths can be used as argumentation (dalil) in the religious life of Muslims or not. Throughout history, epistemology of Hadith studies has been recognized by Muslims and there is no significant resistance from ancient times to the present, accept from the Orientalists who had rejected Hadith criticism methodology proposed by Scholars of Hadith. The Orientalists who were skeptical of the authenticity of Prophet Hadith that appeared since the second half of the nineteenth century AD, as if they had tried to break down the foundations of Hadith epistemology through their premise, concept, and conclusions. Facing such orientalist attitudes, this paper tries to offer four concepts, critical and scientific attitude, constructive and not destructive thinking, based thinking on the basic concept of the Koran, and using the method of thinking balancely and proportionally. Keywords: epistemology, the study of Hadith, sanad, matn, riwayah, dirayah, Hadith Scholars, Orientalists, the authenticity of Hadith.